Histone Deacetylase SIRT1, Smooth Muscle Cell Function, and Vascular Diseases - Wang, Fang; Chen, Hou-Zao (Frontiers in Pharmacology, 2020)
Vascular smooth muscle cells (VSMCs), located in the media of artery, play key roles in maintaining the normal vascular physiological functions. Abnormality in VSMCs is implicated in vascular diseases (VDs), including atherosclerosis, abdominal aortic aneurysm (AAA), aortic dissection, and hypertension by regulating the process of inflammation, phenotypic switching, and extracellular matrix degradation. Sirtuins (SIRTs), a family of proteins containing seven members (from SIRT1 to SIRT7) in mammals, function as NAD+-dependent histone deacetylases and ADP-ribosyltransferases. In recent decades, great attention has been paid to the cardiovascular protective effects of SIRTs, especially SIRT1, suggesting a new therapeutic target for the treatment of VDs. In this review, we introduce the basic functions of SIRT1 against VSMC senescence, and summarize the contribution of SIRT1 derived from VSMCs in VDs. Finally, the potential new strategies based on SIRT1 activation have also been discussed with an emphasis on SIRT1 activators and calorie restriction to improve the prognosis of VDs.